Developing Minahasa Culinary Competitive Strategy using Information Technology - Tangkere, Telly (JR Education, 2025)
The Minahasan culinary tradition represents a unique cultural asset of Indonesia, characterized by distinctive flavors, cooking techniques, and local ingredients. However, its competitiveness faces challenges in the digital era, including limited adoption of information technology, restricted access to digital markets, and growing competition from global franchises. This study aims to develop a competitive strategy model for Minahasan cuisine by integrating information technology to strengthen its sustainability and market positioning. Employing a sequential exploratory mixed-methods approach, qualitative data were collected through in-depth interviews with culinary entrepreneurs, industry experts, academics, and local government representatives, while quantitative data were obtained from surveys of entrepreneurs and consumers to assess technology adoption and competitiveness factors. Digital data from social media, online food delivery platforms, and Google Trends were analyzed to capture market dynamics. The findings reveal that digital marketing, product innovation, online platform optimization, and data-driven management are key factors enhancing competitiveness. The developed model integrates the Business Model Canvas, SWOT Analysis, and Blue Ocean Strategy, emphasizing three dimensions: product innovation, digital transformation in marketing, and ecosystem collaboration involving government, culinary associations, and tourism stakeholders. This model provides both academic contributions to the field of digital culinary business strategy and practical recommendations for policymakers and local entrepreneurs to leverage technology in sustaining and expanding Minahasan culinary heritage. The study concludes that embedding digital transformation within culture-based differentiation can generate a sustainable competitive advantage, enabling Minahasan cuisine to thrive in national and global markets